Shallow P-wave seismic reflection event for estimating the static time corrections: implications for 3D seismic structural interpretation, Ellis County, Kansas - Tucci, Christian (Kansas State University, 2019)
In a processing flow of 2D or 3D seismic data, there are many steps that must be completed in seismic processing to produce a dataset in suitable for seismic interpretation. In case of land seismic data, it is very essential that the data-processing work flow create and utilize a static time correction to eradicate variations in arrival time associated with changes in the topography and low-velocity near surface geology (Krey 1954). This project utilizes velocity analysis, based on a near-surface reflection, to estimate near surface statics corrections to a datum at elevation of 1300 ft (Sheriff and Geldart 1995, Rogers 1981). Reviewing and Rectifying errors in geometrical aspects of the field seismic data is essential to the validity of velocity analysis and estimation. To this end, geometrical aspects of the data were validated based on spatial aspects of the survey acquisition design and acquired data attributes. The seismic workflow is a conglomeration of many steps, of which, none should be overlooked or given insufficient attention. The seismic processing workflow spans from loading the data into a processing software with the correct geometry to stacking and binning the traces for exportation to interpretation software as a seismic volume. Important steps within this workflow and ones that will be covered in this thesis include; the framework to reverse engineer a survey geometry, dynamic corrections, velocity analysis, and building of a static model to account for the near surface, or low velocity layer. This seismic processing workflow seeks to quality control most, if not all, seismic datasets in hopes to produce higher quality and more accurate three-dimensional seismic volumes for interpretation. The developed workflow represents cost-effective, rapid approach of improving the structural fidelity of land seismic data in areas with rugged topography and complex near-surface velocity variation (Selem 1955; Thralls and Mossman 1952).
Keywords: Seismic processing; Geophysics; Geology; Quality control